[Comment] Efficacy of FOLFIRI plus cetuximab vs FOLFIRI plus bevacizumab in 1st-line treatment of older pa tients with RAS wild-type metastatic colorectal cancer:an analysis of the randomised trial FIRE-3 - Wu Deqing (结直肠肛门外科)
[Background] The evidence on the efficacy of anticancer therapy is limited in older patients with metastatic colorectal cancer (mCRC). This retrospective analysis of phase III FIRE-3 trial assesses the efficacy of FOLFIRI plus either cetuximab or bevacizumab according to the patients' age and sidedness of primary tumour. [Methods] The study endpoints overall response rate (ORR), progression-free survival (PFS) and overall survival (OS) were compared between younger (<65 years) and older (≥65 years) patients, followed by stratification according to primary tumour sidedness. ORR was compared using Fisher´s exact test, OS and PFS were estimated by the Kaplan-Meier method and compared using the log-rank test. Univariate Cox regression analyses assessed hazard ratios and 95% confidence intervals for OS and PFS. [Results] Overall, older patients with RAS WT tumours had a significantly shorter OS when compared to younger patients (25.9 months vs 29.3 months, HR 1.29; P = 0.02). Also the proportion of right-sided tumours was significantly greater in older patients (27.1% vs 17.9%; P = 0.029). Secondary resection rates were numerically higher in younger patients (25.4% vs. 17.6%, P = 0.068) than in older patients. This was primarily seen in the Cetuximab arm, where older patients underwent less likely resection (13.1% vs. 26%; P = 0.02). Older patients with left-sided tumours showed only a trend towards greater efficacy of cetuximab (HR 0.86; P = 0.38). In patients with right-sided primary tumours, older patients did not appear to benefit from cetuximab in contrast to younger patients (≥65 years: 16.6 months vs 23.6 months, HR 1.1; P = 0.87; <65 years: 21.9 months vs 16.4 months HR 1.5; P = 0.31). [Conclusions] In FIRE-3, OS was generally shorter in older patients in comparison to younger patients. This could be explained by the overrepresentation of right-sided tumours and a lower secondary resection rate in older patients. The efficacy of targeted therapy was dependent on tumour sidedness in older patients with RAS WT mCRC.